Vitamin D insufficiency and deficiency and mortality from respiratory diseases in a cohort of older adults: potential for limiting the death toll during and beyond the COVID-19 pandemic? - Brenner, Hermann; Holleczek, Bernd; Schöttker, Ben (Nutrients, 2020)
The COVID-19 pandemic goes along with increased mortality from acute respiratory disease. It has been suggested that vitamin D3 supplementation might help to reduce respiratory disease mortality. We assessed the prevalence of vitamin D insufficiency and deficiency, defined by 25-hydroxyvitamin D (25(OH)D) blood levels of 30–50 and <30 nmol/L, respectively, and their association with mortality from respiratory diseases during 15 years of follow-up in a cohort of 9548 adults aged 50–75 years from Saarland, Germany. Vitamin D insufficiency and deficiency were common (44% and 15%, respectively). Compared to those with sufficient vitamin D status, participants with vitamin D insufficiency and deficiency had strongly increased respiratory mortality, with adjusted hazard ratios (95% confidence intervals) of 2.1 (1.3–3.2) and 3.0 (1.8–5.2) overall, 4.3 (1.3–14.4) and 8.5 (2.4–30.1) among women, and 1.9 (1.1–3.2) and 2.3 (1.1–4.4) among men. Overall, 41% (95% confidence interval: 20–58%) of respiratory disease mortality was statistically attributable to vitamin D insufficiency or deficiency. Vitamin D insufficiency and deficiency are common and account for a large proportion of respiratory disease mortality in older adults, supporting the hypothesis that vitamin D3 supplementation could be helpful to limit the burden of the COVID-19 pandemic, particularly among women.